2012
DOI: 10.1111/ina.12005
|View full text |Cite
|
Sign up to set email alerts
|

Co-occupant's exposure to exhaled pollutants with two types of personalized ventilation strategies under mixing and displacement ventilation systems

Abstract: Personalized ventilation (PV) system in conjunction with total ventilation system can provide cleaner inhaled air for the user. Concerns still exist about whether the normally protecting PV device, on the other hand, facilitates the dispersion of infectious agents generated by its user. In this article, two types of PV systems with upward supplied fresh air, namely a chair-based PV and one kind of desk-mounted PV systems, when combined with mixing ventilation (MV) and displacement ventilation (DV) systems, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 24 publications
3
59
0
1
Order By: Relevance
“…Studies finding that DV and UFAD perform better than MV demonstrated that the vertical diluting function of DV and UFAD can reduce the horizontal dispersion of exhaled flows and can thus reduce the risk of cross‐infection. This finding was found to be valid not only for tracer gas but also for small particles <5 μm in diameter …”
Section: Current Understanding Of Airborne Transmission Indoorssupporting
confidence: 60%
See 2 more Smart Citations
“…Studies finding that DV and UFAD perform better than MV demonstrated that the vertical diluting function of DV and UFAD can reduce the horizontal dispersion of exhaled flows and can thus reduce the risk of cross‐infection. This finding was found to be valid not only for tracer gas but also for small particles <5 μm in diameter …”
Section: Current Understanding Of Airborne Transmission Indoorssupporting
confidence: 60%
“…Past studies that have evaluated the influence of MV, DV, and UFAD on airborne transmission reported some inconsistent findings. Some studies suggested that DV and UFAD are better at reducing the risk of cross‐infection than MV, whereas other studies show that MV performs better than DV and UFAD. Studies finding that DV and UFAD perform better than MV demonstrated that the vertical diluting function of DV and UFAD can reduce the horizontal dispersion of exhaled flows and can thus reduce the risk of cross‐infection.…”
Section: Current Understanding Of Airborne Transmission Indoorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments done in this study represent such scenarios, and all the experimental conditions are with 90% recirculated air. Even though in most of the previous work, the given definition of iF was used in situations where the concentration in background supply air is zero (Li et al 2013), the definition of iF is equally valid in the present situation with 90% recirculated air because the measured background concentration is not due to pollutants from other sources except the infected manikin.…”
Section: Effect Of Recirculation On If Computation and Analysismentioning
confidence: 99%
“…The performance of ventilation and air distribution systems not only influences the indoor air quality directly [11,12], but also strongly affects the total energy consumptions in buildings [13]. Among the evaluation indices referring to ventilation and air distribution systems, there are airflow patterns (such as trajectory, impingement, separation, circulation, reattachment, buoyancy, vortices etc) and airflow field (temperature, velocity and pressure).…”
Section: Introductionmentioning
confidence: 99%